The impact of FDI on ecological unequal exchange in China’s manufacturing industry - Gong, Mengqi; Wang, Longle; Li, Xiaofan (Frontiers in Environmental Science, 2023)
This paper uses the panel data of manufacturing subdivision industry from 2000 to 2014 to calculate the exchange of ecological inequality through MRIO model. On this basis, the systematic GMM model is used to investigate the direct and indirect effects of FDI on the unequal exchange of manufacturing ecology.In addition, the ecological unequal exchange in China's manufacturing industry is decomposed into ecological unequal exchange on the production side, on the consumption side, with developed regions and with lessdeveloped regions .The study finds that: (1) Industry-wide research indicates that FDI inflows have a significant positive impact on reducing the unequal exchange in the manufacturing sector. This finding contributes to the existing literature on the effects of FDI on ecological inequality.(2) Path-specific studies reveal that FDI primarily reduces ecological inequality in the manufacturing sector through technological effects. However, the scale and structural effects of FDI exacerbate ecological inequality, confirming the findings of some scholars. This nuanced understanding of the effects of FDI on ecological inequality adds to the existing body of research.(3) From the perspective of FDI sources, FDI from Asian countries and regions is more beneficial for improving China's ecological unequal exchange. This finding provides guidance for China's FDI attraction policies.(4) Assessing pollution emissions inventories based on the principle of production responsibility is unfair to China from both the production and consumption perspectives.(5) From a regional perspective, FDI effectively reduces the impact of ecological unequal exchange in the manufacturing sector between China and developed economies. These findings confirm that China bears an unequal exchange in the trade process and enrich the understanding of the impact of FDI on ecological unequal exchange.